Yield loss of Oryza glaberrima caused by grain shattering under rainfed upland conditions - Montcho, D.; Futakuchi, K.; Agbangla, C.; Fofana, M.; Dieng, I. (African Journals Online, 2013)
The general perception of Oryza glaberrima as low yielding is a potential drawback to intraspecific breeding of this species. Yields of 21 O. glaberrima accessions were evaluated alongside four O. sativa check varieties under two conditions in which panicles were both covered by paper sacks to avoid grain shattering (potential yield plot) and also not covered (control plot) in a rainfed upland field of Benin in 2010 and 2011. Average potential yields of O. glaberrima with panicles covered were 2.42 and 3.65 t ha-1 in 2010 and 2011, respectively, while those of O. sativa were respectively 2.99 and 3.49 t ha-1. Although there was no significant difference between potential yield and control yield in O. sativa, 19 O. glaberrima accessions showed significant yield reduction by grain shattering — the average percentages of lost yield by shattering were 57.88% in 2010 and 66.76% in 2011. These results suggest that low yield of O. glaberrima is due to grain shattering and that its potential yield would not be inferior to O. sativa if the grain shattering problems were overcome. Two O. glaberrima accessions, TOG 12303 and TOG 9300, possessing strong resistance to grain shattering comparable to O. sativa checks, were identified.